Probability Models in Medicine and Biology: Avenues for Their Validation for Humans in Real Life - Neyman, Jerzy (Management Science, 1979)
This paper represents the text of a lecture invited by The Institute of Management Sciences (TIMS). In nontechnical terms it explains certain pitfalls involved in real life public health studies concerned with exposures to low-level irradiation. Two particular recently-announced studies are discussed. The first of them is the study of health effects, particularly cancer, connected with radiation from uranium mill tailings. It is connected with the enactment in November 1978 of Public Law 95-604. The second study was announced last May. It is connected with the accident at the Three Mile Island A-plant. While both studies are irradiation oriented, the validity of their conclusions requires taking into account the exposure to noxious chemical pollutants.